INTERNATIONAL LEGAL FRAMEWORK ON HUMAN TRAFFICKING AND CRIMINAL LIABILITY ON TRAFFICKERS - Paul Nwala (International Studies Journal)
Human trafficking involves recruitment, harbouring or transporting people into a situation of exploitation through the use of violence, deception or coercion and forced to work against their will. People can be trafficked for many different forms of exploitation such as forced prostitution, forced labour, forced begging, forced criminality, domestic servitude, forced marriage, and forced organ removal. It has become a serious global problem that despite legal efforts so far put in place to combat, it has continued to persist. This paper aimed at examining the concept of human trafficking as a crime and analyzing the criminal liability on traffickers in order to ensure that it is the perpetrators of does not go unpunished.. This paper buttresses that human trafficking is not limited to areas of conflict and for sex exploitation. Human trafficking can occur anywhere there is demand for labour. The limitations of international frameworks that exists towards the fight against Human Trafficking are also analyzed. Human trafficking, as recognised in the Declaration of the High-level Meeting on the Rule of Law Trafficking in Persons, preys on the vulnerability of victims and can be considered as a premeditated crime. The United Nations Office on Drugs and Crime (UNODC), as guardian of the United Nations Convention against Transnational Organized Crime (UNTOC) and the Protocols thereto, assists States in their efforts to implement the Protocol to Prevent, Suppress and Punish Trafficking in Persons (Trafficking in Persons Protocol). This paper adopted the content analysis research method. Data was gathered and analyzed critically from various sources, including Anti[1]Trafficking Review Journals and UNODC reports as well as other writers and reportson human trafficking and criminal liability. This study recommends that states should cooperate in fighting the crime of trafficking in persons through the application of international law and ensure that no trafficker goes unpunished. There should be consistency and consensus around the world on the phenomenon of trafficking in persons. In conclusion, domestic legislation on Human Trafficking does not need to follow the language of the Trafficking in Persons Protocol precisely, but should be adapted in accordance with domestic legal systems to give effect to the concepts contained in the Protocol.